Isolation, Detection and Genomic Differentiation of Vibrio cholerae and Vibrio parahaemolyticus in Bachok, Kelantan - B., Vimala; Thong, Kwai Lin; V. C., Chong (Malaysian Journal of Science, 2010)
The objective of this study was to determine the genetic diversity and virulence factors of Vibrio cholerae and V. parahaemolyticus from selected aquatic environments in Bachok, Kelantan, Malaysia. Out of 50 water samples, 33 were confirmed with the presence of presumptive V. cholerae and V. parahaemolyticus based on biochemical tests. Primers targeting toxR gene specific for V. cholerae (800bp) and V. parahaemolyticus (368bp), tdh (251bp) and trh (250bp) virulence genes were used in the PCR. Results of PCR showed that only 25 isolates of V. parahaemolyticus and 3 of V. cholerae had the toxR gene. None of the V. parahaemolyticus isolates had the trh and tdh genes. Repetitive extragenic palindromic PCR (REP-PCR) was used to determine the relatedness of these strains at the genomic level. Cluster analysis for REP-PCR showed 2 major clusters A-B, with several isolates from different locations grouped together indicating the geographical relatedness due to interconnected waterways. REPPCR showed that the species of Vibrios are genetically diverse.